Sexual function in men and women after anterior surgery for chronic low back pain - Hägg, Olle (Springer-Verlag, 2005)
Sexual dysfunction after anterior lumbar fusion has mainly been focused on male biological function (retrograde ejaculation). The aim of the present study is to assess the effect of fusion surgery for chronic low back pain on the sex-related quality of life. Apart from routine prospective questionnaires, additional gender-specific mailed questionnaires produced retrospective data on sexual enjoyment and function after 2 years of follow-up. Patients randomised to non-surgical treatment and anterior or posterior fusion were compared. We found that surgically treated patients had a significantly better sex life than those non-surgically treated. The improved sex life was significantly associated with the reduced back pain. The improvement after anterior fusion, however, was counteracted by a trend towards disturbed orgasm and genital sensation in women, and a significant disturbance of ejaculation and genital sensation in men. In view of the increased frequency of anterior lumbar surgery with the strong promotion of disc replacement, the findings in the present small retrospective pilot study should be tested in larger prospective trials.